Warunki hydrogeologiczne i stan środowiska naturalnego gminy Czarna, powiat dębicki - Nosal, Paulina (My University, 2012)
Aim of this study is to determine the hydrogeological conditions and a state of natural environment the municipality of Czarna. The work contains a description of the geology of the municipality in question, and the characteristics of water-bearing floors. Indirectly, the work has been evaluated in the state of water quality in the area of the municipality. They were presented of the sources of pollution and a state of water and sewage in the municipality. Presented the threat of groundwater and surface water. Hydrogeological map quaternary of water-bearing level, and of the sources of pollution.

Celem pracy jest określenie warunków hydrogeologicznych i stanu środowiska naturalnego gminy Czarna. Praca zawiera opis budowy geologicznej omawianej gminy oraz charakterystykę pięter wodonośnych. Pośrednio w pracy został oceniony stan jakości wód w obszarze gminy. Zostały przedstawione ogniska zanieczyszczeń oraz zaprezentowano stan gospodarki wodno-ściekowej w obszarze gminy. Przedstawiono zagrożenia wód podziemnych i powierzchniowych. Sporządzona została mapa hydrogeologiczna czwartorzędowego poziomu wodonośnego wraz z ogniskami zanieczyszczeń.
Hydrogeological conditions and a state of natural environment Czarna community, administrative district dębicki
mapa, profile (3, cdr, pdf)
Keywords: warunki hydrogeologiczne; zlewnia; jakość wód; stan środowiska naturalnego; gmina Czarna; hydrogeological conditions; catchment; water quality; state of natural environment; municipality of Czarna